2020
DOI: 10.1007/s00464-020-07876-y
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative impedance planimetry (EndoFLIP™) results and development of esophagitis in patients undergoing peroral endoscopic myotomy (POEM)

Abstract: Introduction Peroral endoscopic myotomy (POEM) is a minimally invasive treatment for achalasia. Considerable evidence demonstrates a high incidence of gastroesophageal reflux disease (GERD) after POEM. The endoluminal functional lumen imaging probe (FLIP) uses impedance planimetry to obtain objective measurements of the gastroesophageal junction. This study aims to determine whether FLIP measurements collected at the time of POEM are associated with the development of reflux esophagitis postoperatively. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 42 publications
(76 reference statements)
0
14
0
1
Order By: Relevance
“…3 FLIP has been shown to predict treatment outcomes and have a role in tailoring foregut interventions such as per-oral endoscopic myotomy (POEM) or laparoscopic Heller myotomy (LHM). 15,16 In a study of 143 patients undergoing POEM, intraoperative use of FLIP during POEM resulted in additional real-time myotomy in 65% of cases and improved clinical outcomes compared with scenarios when intraoperative FLIP was not used. 17 Studies have also identified that FLIP performs superiorly to HRM in evaluation of bolus emptying against the gold standard of barium esophagram.…”
Section: Functional Lumen Imaging Probementioning
confidence: 99%
“…3 FLIP has been shown to predict treatment outcomes and have a role in tailoring foregut interventions such as per-oral endoscopic myotomy (POEM) or laparoscopic Heller myotomy (LHM). 15,16 In a study of 143 patients undergoing POEM, intraoperative use of FLIP during POEM resulted in additional real-time myotomy in 65% of cases and improved clinical outcomes compared with scenarios when intraoperative FLIP was not used. 17 Studies have also identified that FLIP performs superiorly to HRM in evaluation of bolus emptying against the gold standard of barium esophagram.…”
Section: Functional Lumen Imaging Probementioning
confidence: 99%
“…4,[14][15][16][17] Importantly, the intraprocedure EndoFLIP measurement showing a higher distensibility index (≥2.7) and higher crosssectional area (≥83) are more likely to develop in post-POEM reflux esophagitis. 49 Use of an intraprocedure EndoFLIP can be used to guide the need for endoscopic fundoplication during the index POEM procedure. 50 As less than half of patients after POEM have symptomatic and objective evidence of GERD and most are managed by PPI only, there is concern regarding the combination of POEM and transoral incisionless fundoplication in every patient.…”
Section: Management Of Post-poem Gerd Tailored To Acidification Patternsmentioning
confidence: 99%
“…Es importante definir cuál es el tipo de trastorno del esfínter esofágico inferior, ya sea acalasia u obstrucción al tracto de salida de la unión esofagogástrica (OTSUEG); se debe disminución de la presión del esfínter esofágico inferior medidos en la MAR (21,28,29); además, el trabajo de Campagna y colaboradores demostró que el UGE-ID no se afecta durante la anestesia general (30). De esta forma, la EndoFLIP permite establecer durante el procedimiento, si se requiere, una mayor dilatación o longitud de la miotomía hasta lograr un incremento del UGE-ID; de modo que se logra una mejor respuesta al tratamiento y disminuye el riesgo de reflujo gastroesofágico (31,32).…”
Section: Disfagia Y Obstrucción Al Tracto De Salida De La Ugeunclassified